Proterozoic highly siderophile element enrichment of the Kaapvaal cratonic Archean mantle - Nadine P. Cooper; D. Graham Pearson; Andreas Auer; Tristan Bongartz; Yannick Bussweiler; Mario Fischer-Gödde; Max Hellers; Geoffrey Howarth; Andrew J. Locock; Ambre Luguet; Carsten Münker; Thomas Stachel; et al. (Chemical Geology, 2026)

Composition and sampling depth of olivine in carbonate-rich olivine lamproites of the Kaapvaal craton - Merrily M. Tau; Geoffrey H. Howarth; Andrea Giuliani; Sinelethu Hashibi (Mineralogy and Petrology, 2025)
Olivine represents the main constituent (40–50 vol%) of carbonate-rich olivine lamproites (CROL) and their xenocrystic cores offer great potential for characterizing the sub-continental lithospheric mantle (SCLM). We present electron probe microanalysis (EPMA) and laser ablation-inductively coupled plasma-mass spectrometry (LA-ICP-MS) data for olivine cores and rims from 11 on-craton CROL localities from the Kaapvaal craton. Olivine xenocrysts are predominantly Mg-rich [Mg# > 89; Mg# = 100 × Mg/(Mg + Fe)], constituting > 95% of the olivine core population. Cores with Mg# of 93–95 and low Ca (< 400 ppm) are unusually abundant in the CROLs, indicating sampling of highly refractory SCLM. Except for the localities Star and Marsfontein, peridotitic olivines from near the lithosphere-asthenosphere boundary (LAB) are rare, and the SCLM is sampled mainly up to ~ 180 km, consistent with the scarcity of deeply derived Cr-poor olivine megacrysts and sheared peridotites. CROLs that sample harzburgitic olivine from the deep lithosphere (> 160 km) feature high diamond grades. Assuming lamproite derivation from the bottom of the lithosphere or deeper, the 160–220 km depth interval beneath the localities Bellsbank, Klipspringer, and Roberts Victor, which show main olivine sampling modes at < 160 km, is likely dominated by eclogite lithologies which is in line with the record of xenoliths and diamond inclusions. Parental melts of the CROLs likely assimilated SCLM components, a process which influenced melt Mg# and the budget of Mn, Co, Zn, Li, and Ti in olivine based on the observed correlation between average core and rim compositions. Conversely, the concentrations of Al, Na, Ca, and Cu in magmatic olivine rims and, therefore, lamproite melts appear to be related to the thermal conditions (and entrainment depth) of the assimilated SCLM.

Neoproterozoic kimberlite and lamproite magmatism of the Man Craton, Liberia, from a common sub-lithospheric source - Njabulo Ndimande; Geoffrey H. Howarth; Andrea Giuliani; Philip E. Janney; Petrus le Roux; Marcel Guillong; Quentin Charbonnier; Stephen E. Haggerty (Mineralogy and Petrology, 2025)
It has been proposed that, rather than the lithosphere, cratonic lamproites may be derived from convecting mantle sources like those of kimberlites, but with extensive subsequent melt modification via melt-rock reaction with metasomatized, phlogopite-rich sub-continental lithospheric mantle (SCLM). Here we explore this model using samples from kimberlite (Camp Alpha) and olivine lamproite (Weasua) localities in Liberia, West Africa. U–Pb dating of perovskite, performed using in-situ Pb isotope compositions of coexisting (low U/Pb) mica, provides broadly coeval Neoproterozoic ages for Camp Alpha (762 ± 9 Ma) and Weasua (779 ± 6 Ma and 754 ± 7 Ma), indicating emplacement during break-up of the supercontinent Rodinia. The mineralogy and mica compositions along with bulk-rock geochemistry of Camp Alpha kimberlites are consistent with derivation from a sub-lithospheric mantle source. The Weasua lamproite contains perovskite with trace element concentrations (e.g., Sr < 3000 µg/g), trace element ratios (e.g., Th/U, Th/Nb, and La/Nb), and 87 Sr/ 86 Sr values (0.7029 to 0.7030) that overlap those of perovskite in the Camp Alpha kimberlites ( 87 Sr/ 86 Sr = 0.7028 ± 0.0002). These data are also similar to those of perovskite in worldwide Neoproterozoic to Cambrian-aged kimberlites but distinct from typical cratonic lamproites, which exhibit perovskite with high Sr contents (> 4000 µg/g) and Sr isotope signatures typical of the enriched lithospheric mantle (bulk-rock 87 Sr/ 86 Sr i generally > 0.7050). A possible petrogenetic model for the Weasua lamproites entails derivation from a sub-lithospheric source similar to that of the Camp Alpha kimberlites with mineralogical, and hence major-element, variations between these two proximal localities driven by variable assimilation of heterogeneous SCLM material.

A review of olivine as a tool for understanding kimberlite petrogenesis and diamond potential - Geoffrey H. Howarth; Federico Casetta; Adam Abersteiner (Mineralogy and Petrology, 2025)
Olivine, the most abundant mineral in kimberlites, exhibits complex compositional zoning characterised by xenocrystic mantle-derived cores that are surrounded by numerous growth and equilibration zones. This review explores how olivine can be used to understand magma evolution, mantle sampling depths, and assess the diamond potential of kimberlites. Aluminium-in-olivine thermometry of xenocryst cores, calibrated against local geotherms, provides valuable insights into the peridotitic material sampled by kimberlites, including its diamond potential. By analyzing the relative abundance of peridotitic- versus megacrystic-derived olivine core zones in individual kimberlites, the extent of diamond-destructive preconditioning by proto-kimberlite melts within the sub-continental lithospheric mantle (SCLM) can be evaluated. Global compilations of mean core and rim compositions, along with groundmass modal abundances, help to understand the diversification of kimberlite melts through complex interactions with SCLM. Similarly, global data on cratonic olivine lamproites indicate that they evolved from sub-lithospheric melts, diversifying within the SCLM to produce the observed range of cratonic lamproite compositions. Crystal inclusions within olivine allow for the liquid line of descent to be constrained, and chemical gradients at the interface between cores and growth zones in olivine allow the application of chronometry models for estimating the ascent rate of kimberlites from the mantle to the surface. Additionally, primary and secondary melt/fluid inclusions offer snapshots of kimberlite melt compositions, tracing melt evolution across multiple stages. Thus, olivine allows for unprecedented insight into the nature of the SCLM sampled by kimberlite magmas, as well as their formation and evolution from source to surface.

Selected papers of the 12th International Kimberlite Conference - Thomas Stachel; D. Graham Pearson; Sonja Aulbach; Barrett Elliott; Geoffrey H. Howarth; Kelly R. Russell; Karen V. Smit; Lutz Nasdala (Mineralogy and Petrology, 2025)

Kimberlite pre-conditioning of the lithospheric mantle and implications for diamond survival: a case study of olivine and mantle xenocrysts from the Koidu mine (Sierra Leone) - Geoffrey H. Howarth; Andrea Giuliani; Yannick Bussweiler; Merrily Tau; Sinelethu Hashibi; Philip E. Janney; Tom E. Nowicki (Mineralium Deposita, 2025)
The diamond potential of kimberlites is generally determined using indicator minerals (i.e., xenocrysts), entrained by the parent magma while ascending through the sub-continental lithospheric mantle (SCLM). It is becoming increasingly apparent that olivine can also be used to understand mantle sampling depth, using the Al-in-olivine thermometer, and to constrain the extent of diamond-destructive metasomatism in the SCLM. To further current understanding of vertical sampling and diamond preservation in the SCLM, we present geochemical results for kimberlitic olivine of the Koidu mine (Sierra Leone). We combine our olivine data with pressure-temperature estimates from available olivine diamond inclusions, clinopyroxene xenocrysts, and eclogite xenoliths to visualise the vertical distribution of lithologies in the SCLM beneath Koidu. In agreement with the absence of peridotitic olivine and low abundance of olivine diamond inclusions in the lower SCLM, megacrysts appear to dominate the material sampled from the lowermost lithosphere. At shallower levels a distinct eclogite-dominated region is observed (160-180 km) whereas the SCLM at depths of 110-150 km is heterogeneous comprising depleted harzburgite/dunite, lherzolite, and eclogite. Diamonds are predominantly eclogitic with pressure-temperature estimates for diamondiferous eclogites of 150-190 km within the eclogite-dominated region. The near absence of diamonds sampled from near the lithosphere-asthenosphere boundary is attributed to diamond destruction by extensive infiltration of proto-kimberlite melts leading to metasomatism of the eclogite and peridotite substrate and megacrysts formation. Widespread metasomatism of the deepest reaches of the SCLM sampled by kimberlites elsewhere suggests that Koidu does not represent an isolated case and the extent of diamond-destructive metasomatism can be constrained using olivine xenocrysts.

Oxygen isotope constraints on proto-kimberlite melt modification through assimilation of low δ18O recycled crust in the deep lithosphere - Joshua van Blerk; Geoffrey H. Howarth; Chris Harris; Philip E. Janney (Geochimica et Cosmochimica Acta, 2025)

Petrogenesis and indicator mineral chemistry of the K-richterite- and leucite-bearing diamondiferous Kareevlei Kaapvaal lamproite - Zuko Qashani; Sinelethu Hashibi; Geoffrey H. Howarth; Philip E. Janney; Petrus le Roux; Jock Robey (Lithos, 2024)

Mica Rb-Sr dating by laser ablation ICP-MS/MS using an isochronous calibration material and application to West African kimberlites - Andrea Giuliani; Senan Oesch; Marcel Guillong; Geoffrey H. Howarth (Chemical Geology, 2024)

Petrology of an apatite-calcite segregationary kimberlite from the Andriesfontein pipe, Kaapvaal craton - Geoffrey H. Howarth; Gelu Costin; Chad J. Peel; Zuko Qashani (Lithos, 2023)

The relationship between δ18O values and incompatible element and radiogenic isotope enrichment in the Mashikiri nephelinites, of the Karoo LIP, southern Africa - Chris Harris; Sarah Eriksson; Petrus le Roux; Geoffrey H. Howarth (Lithos, 2023)

Major-, trace-element and Sr-Nd-Hf isotope geochemistry of diamondiferous dykes from Tonguma and Koidu, Sierra Leone: Highly micaceous kimberlites formed by assimilation of metasomatised lithospheric mantle rocks - Angus Fitzpayne; Andrea Giuliani; Geoffrey H. Howarth; Bradley J. Peters; Manuela A. Fehr; Roland Maas (Chemical Geology, 2023)

Constraints on martian depleted shergottite volcanism from the petrogenesis of olivine-phyric shergottites NWA 2046 and NWA 4925 - Chad J. Peel; Geoffrey H. Howarth; James M.D. Day; Petrus le Roux; Olivier Alard (Journal of African Earth Sciences, 2023)

Petrogenesis of the Tuli Basin high-Ti picrites and basalts, Karoo CFB, southern Africa: Classification, stratigraphy, emplacement, and mantle source heterogeneity - Geoffrey H. Howarth; Julian S. Marsh; Andy R. Duncan; Chris Harris; Jussi S. Heinonen; Stephen H. Richardson; Anton le Roex; Richard W. Carlson; Robert E. Zartman (Lithos, 2023)

Rapid characterisation of Mars' mantle reservoirs by in situ laser ablation 87Sr/86Sr analysis of shocked feldspar (maskelynite) - Daniel L. Burgin; James M. Scott; Petrus J. le Roux; Geoffrey Howarth; Marshall C. Palmer; Thomas A. Czertowicz; Marianne Negrini; Malcolm R. Reid; Claudine H. Stirling (Geochimica et Cosmochimica Acta, 2023)

Candidate locus analysis of the TERT–CLPTM1L cancer risk region on chromosome 5p15 identifies multiple independent variants associated with endometrial cancer risk - Luis G. Carvajal-Carmona; Tracy A. O’Mara; Jodie N. Painter; Felicity A. Lose; Joe Dennis; Kyriaki Michailidou; Jonathan P. Tyrer; Shahana Ahmed; Kaltin Ferguson; Catherine S. Healey; Karen Pooley; Jonathan Beesley; et al. (Human Genetics, 2015)

The secondary origin of diamonds: multi-modal radiation tomography of diamondiferous mantle eclogites - Geoffrey H. Howarth; Nikolay V. Sobolev; John F. Pernet-Fisher; Peter H. Barry; Dayakar Penumadu; Stephen Puplampu; Richard A. Ketcham; Jessica A. Maisano; Dawn Taylor; Lawrence A. Taylor (International Geology Review, 2014)

Komsomolskaya diamondiferous eclogites: evidence for oceanic crustal protoliths - John F. Pernet-Fisher; Geoffrey H. Howarth; Yang Liu; Peter H. Barry; Laura Carmody; John W. Valley; Robert J. Bodnar; Zdislav V. Spetsius; Lawrence A. Taylor (Contributions to Mineralogy and Petrology, 2014)